Perkembangan Kerpibadian Remaja - Vera Novrianti; Tasya Amanda Putri; Rahma Dini; Linda Yarni (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine personality development in adolescents, with a focus on the factors that influence this process. Adolescent personality is a critical stage in the formation of individual identity that influences behavior, social relationships and personal achievements. In this context, this study explains the dynamics of adolescent personality development from a psychological and social perspective, as well as its implications for mental health and social adaptation. This research also explores the role of family, school and peer group environments in shaping and changing adolescent personality characteristics. It is hoped that the results of this research will provide a deeper understanding of the journey of adolescent personality development and its implications in supporting overall individual development.